Investigation of Lubrication Effects in the Right Side of the Forming Limit Diagrams - Sener, Bora; Kayali, Eyup Sabri (AMER INST PHYSICS, 2014)
In the present work, effect of lubrications was investigated in the right side of the forming limit diagram (FLD) by using the out-of-plane formability test. Interstitial-free steel (IF) sheet was used in this study. Primarily, mechanical properties of material like yield, tensile strengths, strain hardening coefficient (n), normal and planar anisotropy were determined by tensile test. Then, IF steel sheet was subjected to the out-of-plane formability test using four different lubricants. Polyethylene, Teflon, PVC film and deep drawing oil were used in the experiments. Major and minor strains were measured by image processing technique on the deformed sheets and was determined the right side of the FLD as per these lubricants separately. Deep drawability of IF steel sheet is high because of high normal anisotropy coefficient and while caring tendency during deep drawing is expected to be low due to its low planar anisotropy. It was shown that, the right side of the FLD was changed with these lubricants in out-of-plane formability test and almost biaxial deformation conditions were provided with deep drawing oil.
Keywords: lubrications; forming limit diagram; out-of-plane formability test; interstitial-free (IF) steel; deep drawing oil; SHEET; Physics